STRATEGI MENINGKATKAN MUTU CALON GURU AGAMA ISLAM - Muhammad Munadi; Siti Choiriyah; Noor Alawiyah (Jurnal Pendidikan Islam, 2012)
The aim of the paper is to describe strategy improve the quality of Islamic religious education teacher candidates at some private colleges. The method of the paper was qualitative. Instruments of data collection are observation, interview and document analysis. Analysis used interactive. The result are 1) strengthen islamic science throught mentoring cocurriculer, 2) splitting of Islamic religion learning methodology be a fiqh, akhlaq, and tawheed; 3) applicating of the computer instruction based on internet to up-date the materials of Islamic Religion, 4) involving the boarding school, 5) built think like a teacher and act like a teacher all together more integrated with intra, co, and extracurricular.